2014
DOI: 10.1002/qj.2478
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the impact of the water‐vapour sounding observations from SAPHIR on board Megha‐Tropiques for the ARPEGE global model

Abstract: Data assimilation experiments of radiances from the microwave sounder SAPHIR on board the Megha-Tropiques (MT) satellite were conducted using the global numerical weather prediction (NWP) model ARPEGE (Action de Recherche Petite Echelle Grande Echelle) operational at Météo-France for the period June to August 2012. The combination of the MT's low-inclined orbit with the SAPHIR's six channels was found to increase the number of assimilated humidity-sensitive microwave observations in the Tropics by a factor of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 40 publications
3
29
0
Order By: Relevance
“…For instance, ATMS offers a large suite of channels that can complement each other to separate clear and cloudy scenes (Bormann et al, 2013), while SAPHIR provides only channels in the 183.31 GHz line, giving fewer possibilities for cloud detection (Chambon et al, 2015). Several filtering techniques using only 183 GHz channels exist, relying on the strong reduction in BT induced by scattering and/or absorption, which can reach up to 20 K in regions of intense convection (Greenwald and Christopher, 2002;Hong et al, 2005;Buehler et al, 2007).…”
Section: Water Vapor Analysismentioning
confidence: 99%
“…For instance, ATMS offers a large suite of channels that can complement each other to separate clear and cloudy scenes (Bormann et al, 2013), while SAPHIR provides only channels in the 183.31 GHz line, giving fewer possibilities for cloud detection (Chambon et al, 2015). Several filtering techniques using only 183 GHz channels exist, relying on the strong reduction in BT induced by scattering and/or absorption, which can reach up to 20 K in regions of intense convection (Greenwald and Christopher, 2002;Hong et al, 2005;Buehler et al, 2007).…”
Section: Water Vapor Analysismentioning
confidence: 99%
“…The six MWGEO channels are all rejected when the CIWP exceeds a given predefined threshold. Rejecting the six channels at once mimics the cloud screening of SAPHIR data within the ARPEGE 4D‐Var assimilation system (Chambon et al ., ) which rejects all channels depending on the ice scattering signature in SAPHIR channel 6. The 25 infrared channels from the IRS instrument are significantly affected by both liquid and solid hydrometeors so the selected proxy is an integrated cloud water + cloud ice water path (CIWP + CLWP thereafter CLCIP). This quantity is computed over three nested atmospheric layers: from model top to 300 hPa (CLCIP1), from model top to 600 hPa (CLCIP2) and from model top to the ground (CLCIP3).…”
Section: Observing System Simulation Experiments Frameworkmentioning
confidence: 99%
“…Examples of weighting functions for (a) MHS, (b) SAPHIR, and (c) ATMS for a tropical atmospheric profile at 29°N, 71°W on 1 July 1993 at 0000 UTC from the Chevalier () dataset, showing the increased vertical coverage provided by SAPHIR over the other instruments. (d) and (e) show, respectively, the temperature and specific humidity profile for the point used…”
Section: Introductionmentioning
confidence: 99%
“…Chambon et al . () investigated the impact of SAPHIR radiances in the global numerical weather prediction (NWP) model operational at Météo‐France, Action des Recherche Petit Echelle et Grand Echelle (ARPÈGE); they found that the combination of the MT low inclination orbit with SAPHIR's six channels increased the number of assimilated humidity‐sensitive microwave observations in the Tropics by a factor of 3.8, compared to the control experiment in which three AMSU‐B/MHS microwave sounders were assimilated. Chambon et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation